Static stress analysis of multi-layered soils with twin tunnels by using finite and infinite elements - Yuksel, Yusuf Z.; Akbas, Seref D. (Techno-Press, 2023)
The aim of this paper is to investigate stress analysis of semi-infinite soils consisting of two layers with twin rectangular tunnels under static loads. The region close to the ground surface and tunnel modelled within finite elements. In order to use a more realistic model, the far region is modelled within infinite elements. The material model of the layered soil is considered as elastic and isotropic. In the finite element solution of the problem, two dimensional (2D) plane solid elements are used with sixteen-nodes rectangular finite and eight-nodes infinite shapes. Finite and infinite elements are ordered to be suitable for the tunnel and the soils. The governing equations of the problem are obtained by using the virtual work principle. In the numerical process, the five-point Gauss rule is used for the calculation of the integrations. In order to validate using methods, comparison studies are performed. In the numerical results, the stress distributions of the two layered soils containing twin rectangular tunnels presented. In the presented results, effects of the location of the tunnels on the stress distributions along soil depth are obtained and discussed in detail. The obtained results show that the locations of the tunnels are very effective on the stress distribution on the soils.
Keywords: finite-Infinite elements; multi-layered soils; stress analysis; tunnels